2022
DOI: 10.18178/ijiet.2022.12.12.1758
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Virtual Anatomy Museum: Facilitating Student Engagement and Self-paced Learning through an Interactive Platform

Abstract: Due to the COVID-19 pandemic, digitalization of teaching and learning has been forced to be in place for effective remote and online education. Most learning platforms offer teacher-centered pedagogy and limited opportunities for self-paced learning. This project used Gather. Town, which is an online proximity-based video-conferencing platform with an ability to allow student interactions and self-paced learning. This case study aimed to evaluate Year 1 pharmacy students’ experiences and perceptions in learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A recent scoping review of empirical studies using the Gather.Town platform for educational purposes found that Gather.Town generally increased students’ satisfaction and engagement in a variety of courses including English language learning, , computer science, anatomy, engineering, and statistical analysis . Despite the aforementioned research showing that engagement in social learning spaces is beneficial to students’ understanding of the instructional content in chemistry courses, there have been few examples in the literature of Gather.Town being used for chemistry-related contexts. Furthermore, where Gather.Town has been used in chemistry contexts, it was used as a venue for conference poster sessions, primarily for professional chemists rather than as an instructional platform for students.…”
mentioning
confidence: 99%
“…A recent scoping review of empirical studies using the Gather.Town platform for educational purposes found that Gather.Town generally increased students’ satisfaction and engagement in a variety of courses including English language learning, , computer science, anatomy, engineering, and statistical analysis . Despite the aforementioned research showing that engagement in social learning spaces is beneficial to students’ understanding of the instructional content in chemistry courses, there have been few examples in the literature of Gather.Town being used for chemistry-related contexts. Furthermore, where Gather.Town has been used in chemistry contexts, it was used as a venue for conference poster sessions, primarily for professional chemists rather than as an instructional platform for students.…”
mentioning
confidence: 99%